Keanekaragaman Jenis Lalat Di Tempat Pembuangan Akhir (TPA) Kampung Durian Kabupaten Aceh Tamiang - M Rizky Parliansyah; Inka Faradina; Resa Tiara; Hesti Maharani; Andriana Sheilla (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2023)
Kampung Durian Village is one of the villages in Aceh Tamiang which is located between Rantau and Kualasimpang Districts. This village is a final disposal site for residents' rubbish from several areas. Garbage that has been landfilled can be used by flies as a nest in their breeding process. So research is needed on the diversity of fly species in order to provide information and to assist in the management of the Kampung Durian Final Disposal Site (TPA), Aceh Tamiang Regency, especially in controlling flies at the Final Disposal Site (TPA). This research is exploratory research. The diversity of flies was analyzed descriptively. It will be implemented in October 2023 at the Kampung Durian Final Disposal Site (TPA) and settlements around the Aceh Tamiang Regency TPA. The research results showed that there were 3 species of flies found, namely Musca domestica, Calliphora vomitoria and Condylostylus sipho. Apart from that, the results showed that the diversity of flies in the landfill and its surroundings had a low diversity index, namely 0.5587 because H' 1. This shows that the management of the Kampung Durian landfill, Aceh Tamiang Regency is well managed and does not pollute the surrounding area